Cycloartane triterpenoids and biological activities from the propolis of the stingless bee Lisotrigona furva. Issue 4 (14th August 2021) - Thanh, Le Nguyen; Thoa, Ha Thi; Oanh, Nguyen Thi Tu; Giap, Tran Huu; Quyen, Vu Thi; Ha, Nguyen Thi Thu; Phuong, Diep Thi Lan; Lien, Nguyen Thi Phuong; Hang, Nguyen Thi Minh
Abstract: Chromatographic separation of ethyl acetate extract of the stingless bee Lisotrigona furva propolis, that collected in Khanh Hoa province, led to isolation of five cycloartane‐type triterpenes including cycloartenone (1 ), cycloartenol (2 ), (24 E )‐3 β ‐hydroxycycloart‐24‐en‐26‐al (3 ), mangiferonic acid (4 ) and mangiferolic acid (5 ). Mango plant ( Mangifera indica ) was suggested to be a resin source of the propolis. The propolis EtOH extract showed good antimicrobial activity on Gram (+) strain E. feacalis and fungus C. albicans . Among the isolated compounds, compound 3 displayed selective activity against three Gram (+) strains and C. albicans over Gram (‐) strains with all MIC values of 64 μg/mL. However, the propolis EtOH extract was not active against LU‐1 and MCF‐7 cancer cell lines. Only compound 5 exhibited moderate activity on LU‐1 cancer cell line with IC50 of 13.33 μg/mL.